Demand for Canadian banknotes from international travel: Indirect evidence from the COVID-19 pandemic - Hong Yu Xiao (Bank of Canada, 2024)
Recent trends suggest that domestic demand alone may not be enough to explain the increase in overall demand for Canadian banknotes (Engert et al., 2019). Estimating foreign cash demand is difficult due to data availability issues and confounding factors that simultaneously affect domestic demand. In this paper, I provide a quantitative causal estimate of banknote demand from international visitors to Canada by exploiting the exogenous shock from COVID-19 international travel restrictions, which led to an unprecedented drop in cross-border travel. To identify international visitor demand shocks from contemporaneous domestic demand shocks due to the pandemic, I apply a difference-in-differences strategy, taking advantage of foreign traveler demand's distinct regional patterns and data from the Bank of Canada's Bank Note Distribution System. I find that each international visitor brought on average 165 worth of hundred-dollar notes with them to Canada prior to the pandemic. Under plausible assumptions, total holdings by international visitors constitute roughly 10% of total 100 CAD notes in circulation at the end of 2019.
Keywords: E41; E42; E58; F22; 330; Bank notes; Central bank research; Coronavirus disease (COVID-19); Financial services; International topics